2008
DOI: 10.1016/j.brat.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Threat processing in obsessive-compulsive disorder: Evidence from a modified negative priming task

Abstract: Individuals with obsessive-compulsive disorder (OCD) often experience intrusive thoughts. These intrusions may be due to biases in information processing mechanisms, including attention, memory, and learning. To examine this hypothesis, we presented a modified negative priming (NP) paradigm with idiographically-selected words to 19 individuals with OCD (OCs) and 19 matched non-anxious control participants (NACs). The words included OCD-relevant threat, OCD-relevant positive, and neutral words. This paradigm ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 61 publications
(90 reference statements)
1
8
0
Order By: Relevance
“…Since then, another well-designed study on OCD could not establish reduced negative priming in OCD (MacDonald, Antony, MacLeod, & Swinson, 1999), while yet two others found mixed evidence, depending on prime presentation time (McNally, Wilhelm, Buhlmann, & Shin, 2001), response-to-stimulus interval and illness subtype (Hoenig, Hochrein, Muller, & Wagner, 2002). The most recent study could only establish reduced negative priming for idiographic, OCD-relevant threat information but not for neutral material (Amir, Cobb, & Morrison, 2008). Salience and subjective importance of the threat stimuli likely made it harder for patients to ignore them.…”
Section: Introductionmentioning
confidence: 94%
“…Since then, another well-designed study on OCD could not establish reduced negative priming in OCD (MacDonald, Antony, MacLeod, & Swinson, 1999), while yet two others found mixed evidence, depending on prime presentation time (McNally, Wilhelm, Buhlmann, & Shin, 2001), response-to-stimulus interval and illness subtype (Hoenig, Hochrein, Muller, & Wagner, 2002). The most recent study could only establish reduced negative priming for idiographic, OCD-relevant threat information but not for neutral material (Amir, Cobb, & Morrison, 2008). Salience and subjective importance of the threat stimuli likely made it harder for patients to ignore them.…”
Section: Introductionmentioning
confidence: 94%
“…One important bottom-up process is action tendency, defined as the automatic predisposition to engage in the specific action an object evokes (e.g., reaching out and turning a door handle). Modifying action tendencies to clinically-relevant items has been shown to reduce avoidance and improve treatment outcomes in anxiety disorders and substance use disorders, both featuring unwanted thoughts and behaviors ( Amir et al, 2008 ; Wiers et al, 2011 ). Moreover, OCD patients display enhanced action tendencies even to neutral stimuli ( Dayan et al, 2014 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intrusive and troubling thoughts that cause anxiety and distress (Obsessions), and give rise to behaviors, i.e. repeated to reduce anxiety (Compulsions), are the characteristics of OCD (Amir, Cobb, & Morrison, 2008;Amir, Najmi, & Morrison, 2009); however, these intrusions also occur in healthy individuals without any psychiatric diagnosis. Studies indicated that 80%-99% of the healthy population experience intrusive thoughts and impulses; however, those with OCD are more troubled by these thoughts and impulses, experience them for longer periods, and experience more difficulties ignoring them (Bradley et al, 2016;Calkins, Berman, & Wilhelm, 2013).…”
Section: Introduction Bsessive-compulsivementioning
confidence: 99%